Вплив схеми з’єднання котушок обмотки статора двигуна з ротором, що котиться, на його енергетичні показники - Єгоров, Андрій Володимирович; Маслєнніков, Андрій Михайлович; Дунєв, Олексій Олександрович; Юхимчук, Володимир Данилович (НТУ "ХПІ", 2017)
Представлена 3D модель високомоментного тихохідного двигуна з ротором, що котиться, (ДРК) з аксіальним магнітним потоком, а також показані результати його експериментального дослідження при різних схемах включення котушок обмотки статора, і з використанням шихтованого і масивного осердя роторів. Наведено схему випробувальної установки, побудовано і порівняно механічні характеристики для кожного з варіантів включення котушок обмотки статора.

Purpose. Choice of optimal constructive and technological solutions to create new designs of motors with a rolling rotor (MRR). Methodology. Modeling of electro-magnetic processes, which appeared in MRR, followed by an experimental research. Results. The optimal winding circuit of the MRR is a circuit of the coils through all 6 diodes. In this connection, the mechanical characteristics MRR-50-6 – is the most rigid. Using the rotor core lamination increases the power efficiency up to 20-30%, compared with the massive rotor core, but it is much worse power factor (by 25-35%). In addition, we should take the complication of manufacturing each rotor into account. Originality. MRR is a non-standard machine in which the rotor rolls over the stator surface with has guaranteed eccentricity. Therefore, the process of transferring the torque from the rotor to the shaft is a complex engineering problem, which was successfully implemented during the research. Practical value. A 3D model of a high-torque low-speed MRR with an axial magnetic flux is presented, and the results of its experimental research are shown for various schemes of connection of the stator coils, using a laminated and massive rotor core. The scheme of the test set is given, the mechanical characteristics for each variants of coils connection are plotted and compared.
Influence of the stator coils scheme connection in the motor with a rolling rotor on its energy performance
Keywords: зубці статора; тангенціальний магнітний потік; аксіальний напрямок; сила одностороннього магнітного тяжіння; лінійний струм; потужність; частота обертання; motor with a rolling rotor; circuit connections; massive rotor; lamination rotor; mechanical characteristics; experimental research